The mathematical analysis of a syntrophic relationship between two microbial species in a chemostat - Tewfik Sari; Miled El Hajji; Jérôme Harmand (Mathematical Biosciences and Engineering)
A mathematical model involving a syntrophic relationship between two populationsof bacteria in a continuous culture is proposed. A detailed qualitative analysis iscarried out as well as the analysis of the local and global stability of the equilibria.We demonstrate, under general assumptions of monotonicity which are relevant froman applied point of view, the asymptotic stability of the positiveequilibrium point which corresponds to the coexistence of the two bacteria.A syntrophic relationship in the anaerobic digestion process is proposed as a real candidate for this model.